Preliminary study of feeding response and survival of coptotermes curvignathus on curcumin - Ahmad, F. B. H.; Anuar, S.; Ahmad, A. R.; Sajab, A. S. (1989)
A preliminary study on responses of Coptotermes curvignathus to purefied Curcumin was carried.out. The termiticidal acativities of Curcumin appeared to be dependent on its concentration. A 100% mortality of termites was observed on filter paper treated with 40ppm. of Curcumin after 6 days of exposure